Preparation and Characterization of Solid Lipid Nanoparticles Loaded with Ceylon Citronella Oil as a Potent System for Slow-releasing Mosquito Repellent - Lokuge, C.M.; De Silva, H.I.C.; Weeratunge, H.D.; Premakumara, G.A.S. (University of Colombo, 2024)
Ceylon Citronella oil (CCO) is known to possess mosquito-repellent activity The effecdve use of CCO is limited by its hydrophobic and high volatility profile. This research study focused on developing solid lipid nanoparticles (SLNs) loaded with CCD as a slow-releasing deliver), system.
Keywords: Ceylon Citronella Oil; Mosquito-Repellent; Solid Lipid Nanoparticles